Evaluating the effect of an emerging microwave-assisted induction heating (MAIH) on the quality and shelf life of prepackaged Pacific white shrimp Litopenaeus vannamei stored at 4°C in Taiwan. (March 2022) - Lee, Yi-Chen; Tsai, Yung-Hsiang; Hwang, Chiu-Chu; Lin, Chih-Ying; Huang, Yu-Ru
Abstract: Microwave-assisted induction heating (MAIH) is an emerging alternative technology for shrimp cooking over traditional heating technologies. This study evaluated the effect of the MAIH and boiling in salt solution on the quality and shelf life of prepackaged Pacific white shrimp L . vannamei stored at 4 °C in Taiwan. Samples were treated for 80 s at 130 °C or for 100 s at 90 °C with the MAIH technology, and 130 s at 90 °C with boiling in salt solution, respectively. Cooked shrimps were stored 28 days at 4 °C to determine changes in aerobic plate count (APC), psychrotrophic bacteria count (PBC), color, texture, pH, and total volatile basic nitrogen (TVBN). Results showed that the levels of APC and PBC were not detectable (<2.0 log CFU/g) during first 12 days of storage in samples treated with the MAIH technology, but they slowly increased afterward, reaching to 3.0 log CFU/g on the 28th day of storage, compared to the traditional boiling technology, when the levels of APC and PBC were gradually increased throughout 28 days of storage, exceeding 8.7 log CFU/g at the end of the storage. In terms of color and TVBN, all cooked samples showed a decreasing trend in lightness ( L* ), redness ( a* ), and whiteness ( W ) but an increasing trend in yellowness ( b* ), absolute color difference ( ΔE ), and the TVBN during the storage period. However, these decreasing and increasing trends occurred slower in samples treated by the MAIH than by boiling ( p  < 0.05). In terms of texture, samples treated by the MAIH demonstrated greater hardness and cohesiveness during the storage than samples boiled in salt solution ( p  < 0.05). Compared with traditional boiling method, the treatment of shrimp samples with the MAIH delayed the degradation of color and texture and inhibited the growth of microorganisms during refrigerated storage. Therefore, the MAIH technology offers a potential alternative over boiling method for preventing the deterioration and quality loss of shrimps more effectively and extending the refrigerated shelf life of prepackaged Pacific white shrimps stored at 4 °C. Highlights: Effect of MAIH and boiled heating on quality of shrimp stored at 4 °C were evaluated. The MAIH effectively pasteurized and retarded bacterial growth of shrimp until 12 d. The boiled samples had higher aerobic plate counts and lower physicochemical values. MAIH can delay reduction of color ( L*, a*, W ) and hardness in samples during storage. . Shrimps heated by MAIH maintained lower TVBN and extended shelf life from 8 d to 28 d .